One smart fish: : One world-changing idea - Wormell, Chris (UK : Red Fox, 2011)
Find out how one smart fish can change the world in this sparkling new adventure from Chris Wormell, creator of George and the Dragon.
English
Keywords: Fishes -- Juvenile fiction; Stories in rhyme